The Sculpture Journal. (Liverpool : Liverpool University Press, 1997)
Sculpture Journal is a triannual peer-reviewed academic journal of sculpture published by Liverpool University Press. It was established in 1997 and the editors-in-chief are Elisa Foster, Teresa Kittler, Eckart Marchand, and Emma Payne (wikipedia)
Https://en.wikipedia.org/wiki/Sculpture_Journal
Https://www.liverpooluniversitypress.co.uk/journals/id/74
Engels
Tijdschriften
Keywords: sculptuur